2017
DOI: 10.1002/pra2.2017.14505401012
|View full text |Cite
|
Sign up to set email alerts
|

Trust in qualitative data repositories

Abstract: This paper applies Pirson and Malhotra's (2011) framework for organizational trust to data reuse in an educational context. Their framework delineates stakeholders along two axes: depth of the interactions (e.g., shallow or deep) and the locus of the relationship (e.g., internal or external). We analyzed 139 survey responses and 44 in-depth interviews with users of repositories holding video records of practice. We found that factors such as data quality, co-production of data between the repository and data p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 34 publications
0
9
1
Order By: Relevance
“…9 South African environmental Observation network, cape town, South Africa. 10 Ocean networks canada, University of Victoria, Victoria, canada. 11 Springer nature, London, UK.…”
Section: Context and Historymentioning
confidence: 99%
See 2 more Smart Citations
“…9 South African environmental Observation network, cape town, South Africa. 10 Ocean networks canada, University of Victoria, Victoria, canada. 11 Springer nature, London, UK.…”
Section: Context and Historymentioning
confidence: 99%
“…Various studies have found that transparency is associated with trust of digital repositories 9 . For example, for users of video data, "transparency of repository practices, and especially data curation practices, are important for trust" 10 . Studying the data repository staff perceptions of repository certification, Donaldson, et al 11 , found that the process of acquiring certification contributed to the transparency of their repository, among other benefits.…”
Section: Impact Of the Trust Principlesmentioning
confidence: 99%
See 1 more Smart Citation
“…Trustworthy Repositories Audit and Certification: Criteria and Checklist (TRAC)/ISO 16363 and Data Seal of Approval (DSA) are some well-known efforts to preserve and provide access to trusted content through repository certification. Since Prieto (2009) argued the need to understand trust from users' perspectives, several research studies have also demonstrated how a repository's intermediary role contributes to data reusers' trust (Donaldson and Conway, 2015;Frank et al, 2017;Yakel et al, 2013;Yoon, 2014a). While past studies underscore the significance of users' trust in repository and curation activities, they also present the need to investigate users' trust in the larger context of data reuse.…”
Section: Introductionmentioning
confidence: 99%
“…They also assess the reputation and the competency of the original data collectors or producers (Zimmerman, 2007). Researchers may also contact the original data collector or producer (Niu, 2009a) or assess the trustworthiness of data curators and repositories (Donaldson & Conway, 2015;Frank, Chen, Crawford, Suzuka, & Yakel, 2017;Yoon, 2014a).…”
Section: Literature Reviewmentioning
confidence: 99%